Cultural and Archaeological Heritage, Landscapes and Root Tourism Building the Enhancement of Territories - Stefania Mancuso (Fuori Luogo, 2023)
This paper emphasizes the development of cultural heritage in order to construct a planned, emotional and sustainable use.